EFFICACY OF INTERRUPTED AND MODIFIED DEFERASIROX DOSE AMONG PAEDIATRIC PATIENTS WITH Î’- THALASSEMIA MAJOR AND HIGH ALANINE AMINOTRANSFERASE LEVEL - AL Hafidh, Nashwan M (Journal of Ayub Medical College Abbottabad, 2019)
Background: Abnormal liver function tests lead to interruptions of Deferasirox therapy. The aim of this study is to assess the efficacy of deferasirox dose 30 mg /kg /day in maintaining cardiac protective level of serum ferritin of <2500 ng/ml among patients who received interrupted and modified doses. Methods: A retrospective cohort study was conducted in Ibn Al Atheer paediatric hospital in Mosul city, Iraq, utilizing the monthly reading of serum ferritin level during the period started in February 2013 to march 2014 using documented patients' records. Group A, patients included thirty-five patients with Î²- thalassemia major whose Deferasirox dose of 30 mg/kg/day was interrupted and modified due to ‰¥ 5-fold raise in alanine aminotransferase during any month of the study period. Compared group B patients included 40 children who received constant median deferasirox dose 30 mg/kg/day throughout one year of study period. Serum ferritin and alanine aminotransferase levels were routinely analysed every month among those patients. Results: Interrupted and modified Deferasirox dose of 30 mg/kg/day significantly (p=0.000) increase the frequency of having mean serum ferritin >2500 ng/ml, and was associated with 55 times relative risk of having mean serum ferritin >2500 ng/ml compared to group B with steady median deferasirox dose. Conclusions: Interrupted and modified deferasirox dose of 30 mg/kg/day has a significant adverse effect on cardiac protective level of serum ferritin. Keywords: Deferasirox dose, Î²- thalassemia major, Alanine aminotransferase, Serum ferritin